Hierarchical ordering in light-triggered additive manufacturing - Monti, Joël; Blasco, Eva (Polymer chemistry, 2020)
Additive manufacturing (AM) emerged, in the last decades, as a promising manufacturing technique for the low-cost fabrication of personalised 3D objects. Recently, this technology has been increasingly utilised, both in everyday life and in industry. Among the numerous AM techniques available, light-triggered AM allows for great shape resolution and a smooth surface, while being a relatively fast process. The increasing interest given to AM naturally motivated the development of novel 3D printable materials in order to keep on widening the possibilities of the techniques. Herein, we present an overview of the materials having been recently reported in the field, for which the incorporation of hierarchical ordering was essential to access novel functionalities and properties. In particular, hybrid materials such as fibre- and nanocrystal-reinforced polymeric networks, liquid crystalline materials and metal-organic framework embedded printable materials along with their future prospects will be discussed.